Pneumatic Brushing Machine Automation Design Based On Programmable Logic Controller (PLC) - Yosy Rahmawati; Imelda Uli Vistalinas Simanjuntak; Dian Aprianto (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
In the production of musical instruments, PT Yamaha Music Manufacturing Asia uses wood as the main material with a production process and model that is in accordance with company regulations to produce a quality musical instrument. In the process of producing musical instruments, PT Yamaha Music Manufacturing Asia still uses industrial machines manually. Problems that occur every year the demand for musical instrument production is always increasing, the amount of production demand must of course be balanced with the readiness of capable machines/production tools because the use of manual machines in the production process reduces efficiency. Therefore, in this study the author contributes to making PLC-Based Pneumatic Brushing Machines to increase company productivity by applying automatic production machines. The design of the brushing machine system is carried out using a 3-phase electric motor as a conveyor and brush drive, a solenoid valve as a pneumatic cylinder driver, and a proximity sensor as an object detector (wood) which is controlled using an Omron PLC, as an automatic controller. The operator only puts the wood on the conveyor, then the wood will be cleaned automatically by a brush controlled by PLC. Based on the results of the feasibility test, the overall machine in the production process is running effectively marked by increased production yields and spots on the wooddisappearingr. Pneumatic works optimally in generating air pressure to move industrial engine components, proximity sensors as wood detect cane to detect wood with a maximum distance of 8 mm, and brushes are clean wood with a width of between 200 mm to 700 mm and a wood thickness of 14 mm to 700 mm. d 23mm. The implications manufacture of this hardware implantable to keep pace with the demand for musical instrument production from PT Yamaha Music Manufacturing with the ability of increasingly sophisticated production machines